Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Profitabilitas dan Dampaknya Terhadap Nilai Perusahaan - Chita Mega Mawarni (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to provide an overview of the profitability and corporate value of companies in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period and to determine the effect of Corporate Social Responsibility Disclosure (CSR) on profitability and its impact on corporate value. The operationalization of the variables used in this study is the independent variable, namely Corporate Social Responsibility (CSR) Disclosure, intervening variables, namely Profitability and the dependent variable, which is Company Value. The research method used is descriptive and verification methods. The sampling technique used in this study is non probability sampling with a purposive sampling method. The population of this study amounted to 60 companies and a sample of 6 companies. Analysis of statistical data used in this study uses path analysis. Statistical test results show that the disclosure of Corporate Social Responsibility (CSR) has a significant effect on profitability and firm value. Disclosure of Corporate Social Responsibility (CSR) affects profitability. Profitability has a significant effect on firm value. Disclosure of Corporate Social Responsibility (CSR) affects the value of the company and Disclosure of Corporate Social Responsibility (CSR) affect the value of the company through profitability.